2021
DOI: 10.18093/0869-0189-2021-31-6-792-798
|View full text |Cite
|
Sign up to set email alerts
|

Secretory immunoglobulin A of the respiratory system and COVID-19

Abstract: The main focus in the course of COVID-19 goes on assessing the overall immune response. The role of mucosal immunity in this disease has not been studied sufficiently.The study aimed to analyze published data about secretory IgA as a significant indicator of the mucosal immune response of the respiratory tract in the context of the COVID-19 pandemic.Methods. Articles were identified via PubMed bibliographic database. The time-span of research was two years (2020, 2021).Results. The search identified 54 article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…It was impossible to assess the rate of systemic reactions because the rates of fever were similar (12.4%) in the patients who received and did not receive Immunovac VP4 as part of a combination treatment regimen. The study of safety of Immunovac VP4 confirms previously obtained data that none of the adverse events required discontinuation of the drug course 42 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It was impossible to assess the rate of systemic reactions because the rates of fever were similar (12.4%) in the patients who received and did not receive Immunovac VP4 as part of a combination treatment regimen. The study of safety of Immunovac VP4 confirms previously obtained data that none of the adverse events required discontinuation of the drug course 42 .…”
Section: Discussionsupporting
confidence: 87%
“…Consequently, in patients with moderate severity of COVID-19, the recovery process was accompanied by an increase in the level of sIgA in the nasal and pharyngeal locus on the 30th day of observation, which may subsequently affect both the recovery process and a decrease in the frequency of recurrent diseases. The work of Kryukova et al showed that the administration of Immunovac VP4 to medical workers who had previously suffered COVID-19 (1st group) was accompanied by an increase in the sIgA level in scraping samples from the oropharyngeal mucosa on the 20th and 90th day up to 19.6 [6.0; 83.8] µg/l and 13.6 [7.4; 48.3] µg/l, respectively, compared to medical staff from the 2nd group without prophylactic administration of the immunotropic drug (4.9 [1.9; 7.6] μg/l (p < 0.05) and 1.8 [1.3; 24.7] μg/l (p < 0.05) 42 . It should be noted that the mechanism of action of the Immunovac VP4 vaccine is based on the activation of innate immune effectors and programming the differentiation of T-lymphocytes to Th1 type.…”
Section: Discussionmentioning
confidence: 99%
“…5) intensive active surveillance is needed for the possibility of infection in all countries using the WHO recommended surveillance case definition. 6) preparation for health system resilience in all countries is needed, as is done during seasonal influenza, anticipating severe infections and the course of the disease in the elderly and other populations identified at risk of severe disease (Kryukova et al, 2021) Based on scientific evidence, COVID-19 can transmit from human to human through coughing or sneezing. The people who are most at risk of contracting this disease are people who are in close contact with COVID-19 patients, including those who treat COVID-19 patients.…”
Section: Preliminarymentioning
confidence: 99%
“…Standard recommendations for preventing the spread of infection through regular hand washing using soap and clean water, applying the ethics of coughing and sneezing. In addition, implementing Infection Prevention and Control while in health facilities strategy 1) implementing standard preventative measures for all patients, 2) ensuring initial identification and source control, 3) implementing administrative controls, 4) using environmental and engineering controls, 5) implementing additional empirical steps for patient cases in COVID-19 surveillance and confirmation (Kryukova et al, 2021) In the effort to overcome COVID-19, it is necessary to provide guidance for the community in making efforts to prevent the spread of COVID-19, especially in providing information to the community related to self-isolation in accordance with a circular to increase support and cooperation across sectors and local governments in handling COVID-19 (Bourrianne et al, 2022) Responding to the development of an increasingly widespread epidemic of COVID-19 globally, it is necessary for collaboration from various parties to help disseminate health information in order to protect against the risk of transmission of COVID-19 disease, some things must be done to avoid COVID-19, namely: Nutritious food, adequate rest, drink enough water, use a mask when there are people, wash your hands frequently, do not consume uncooked food, exercise regularly, avoid visiting the animal market or near other animals, if you have a fever, cough and shortness of breath immediately see a doctor Determination of large-scale social restrictions in the DKI Jakarta province in the context of accelerating the handling of COVID-19 (Fadly & Sari, 2020)…”
Section: Preliminarymentioning
confidence: 99%